Consider the geology in hydrogeology (Journal of Nepal Geological Society, 2000)
The term "Hydrogeology" was coined to reflect that in its use one is considering all aspects of the occurrence of groundwater. In recent times, much emphasis has been placed upon development of theories of groundwater flow and the construction of models to explain how water moves through the geological materials of the earth's crust. First there were physical models, later analogue models, and most recently, with the advent of the computer, mathematical models. However, in each stage of model development the underlying problem has been how to represent properly the geological factors that control the occurrence, storage, and movement of groundwater. Thus it behaves us to improve our knowledge of the physical and chemical nature of the rocks, which contain the water, and to apply that knowledge to our exploration for, protection of, and exploitation of the groundwater resources available to us.Aquifers are said to have three broad functions. The first is that of serving as a storage facility for the water in filtrating and moving to the saturated zone; the second is that of serving as a pipeline through which the water moves; and the third is that of affecting the chemical nature of the water. If we are to manage most efficiently the ground water resources of the world, we must consider all three functions as we address the multitude of problems associated with groundwater management. In a broader context we must look at the hydrological cycle in general and must interpret from the geological record the broad outlines of the hydrological cycles of the geological past in order to understand the past and present volumes of groundwater available to us, both on a short-term and on a long-term basis. Climatology and palaeoclimatology give clues to the use of the storage facility; studies of the petrology and petrography of the rocks provide insight into the storage capacity of the aquifers and into the transportation capacity. Petrology and petrography combined with geochemistry indicate something about how groundwater may be chemically affected in its passage through the rocks, and whether or not manmade chemicals added to the water may be removed during transport. Modern stratigraphic and geophysical techniques can enhance our understanding of the geology upon which hydrogeology is based, and geology becomes an important aspect of the equation when consideration is being given to conjunctive use of surface and groundwater.